Financial Inclusion: Cost and Implications in Developing Countries: A Review of the Existing Literature - Ngonyani, Danstun (Journal of Economics Education and Entrepreneurship, 2022)
This article discusses about research reviews of financial inclusion comprehensively in terms of its nature, basic reasons behind financial exclusion, costs and implication of financial exclusion in developing country like Tanzania. The main objective of this study was to review and analyze various published articles related to financial inclusion in developing countries. The study specifically analyzed the extent to which the existing published academic articles have addressed the challenges associated with financial exclusion. Although substantial progress has been made, there is still much to achieve since FinScope survey Tanzania 2017 reports only 16.7% of adult population in Tanzania access to formal banking services. The same report maintains about 28% of adult Tanzanian are completely excluded from accessing financial services. Based on a content analysis, this study analyzed academic articles from demand side, supply side, regulatory and infrastructure and societal barriers. It is found that most developing countries and Tanzania in particular, are still faced by the mentioned challenges to effective financial inclusion. Lack of a clear and explicit policy on strategies toward inclusive finance and absence of explicit consumer protection regulation in Tanzania and other developing countries is yet another challenge. This study therefore suggests that, firstly, government and other stakeholders to establish guiding policy to enhancing financial inclusion efforts. Secondly, Policy makers and financial services providers need to initiate innovative infrastructure systems to enhance extension of financial services to rural areas at affordable operating costs. Thirdly, there is need for establishing and operationalizing consumer protection regulation among financial services providers. Finally, to encourage variety of financial providers, products and technologies to widen individuals and firms access to finance.